309PEvaluation of a pharmacist-led opioid de-escalation (PLODE) program after chemoradiotherapy completion in head and neck cancer patients. (24th November 2019) - Horinouchi, A; Suzuki, S; Kamata, H; Kaneko, A; Fujisawa, T; Ueda, Y; Enokida, T; Ito, K; Okano, S; Makabe, H; Kawasaki, T; Tahara, M
Abstract: Background: It is important to consider that prolonged opioid use or opioid overuse for a patient who completed radiation therapy (RT) can have harmful effects. In 2018, pharmacists working with oncologists at outpatient clinics conducted an opioid de-escalation program for HNC patients who completed radiation therapy (RT) at the National Cancer Center Hospital East (NCCHE). The aim of this retrospective study was to evaluate the feasibility of a pharmacist-led opioid de-escalation (PLODE) program for HNC patients by comparing the outcomes of patients who participated in the PLODE program and those who did not. Methods: This time-series analysis compared the outcomes of patients who participated in the PLODE program after CRT completion between June 2018 and February 2019 and those of patients who completed CRT between June 2017 and March 2018 and did not participate in the program. The PLODE program consisted of (1) number of opioid rescues, (2) patient's complaints and (3) purpose of opioid use to patients based on the WHO Pain Ladder. Results: Sixty-one patients completed CRT between June 2018 and February 2019. Of these 61 patients, 16 (26%) used opioids at the time of CRT completion and participated in the PLODE program. Ninety-three patients completed CRT between June 2017 and March 2018, and 32 patients (34%) used opioids at the time of CRT completion; these patients were evaluated as the control group. Patients who participated in the PLODE program discontinued opioids statistically earlier than those in the control group (median time to opioid discontinuation 11 days vs 24.5 days, HR 0.31, 95% CI 0.16-0.60, p < 0.001). Between the two groups, there were no differences in time to opioid use, maximum opioid dosing, incidence of grade 3 oral mucositis or time to oral mucositis occurrence. No patients in the PLODE group restarted opioid use after opioid discontinuation or escalated opioid dosing due to the worsening of pain. Conclusions: The study showed the feasibility of a PLODE program for HNC patients who completed CRT. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.